Expanding Group Peer Review: A Proposal for Medical Education Scholarship. (February 2017) - Dumenco, Luba; Engle, Deborah L.; Goodell, Kristen; Nagler, Alisa; Ovitsh, Robin K.; Whicker, Shari A.
Abstract : After participating in a group peer-review exercise at a workshop presented by Academic Medicine and MedEdPORTAL editors at the 2015 Association of American Medical Colleges Medical Education Meeting, the authors realized that the way their work group reviewed a manuscript was very different from the way by which they each would have reviewed the paper as an individual. Further, the group peer-review process yielded more robust feedback for the manuscript's authors than did the traditional individual peer-review process. This realization motivated the authors to reconvene and collaborate to write this Commentary to share their experience and propose the expanded use of group peer review in medical education scholarship. The authors consider the benefits of a peer-review process for reviewers, including learning how to improve their own manuscripts. They suggest that the benefits of a team review model may be similar to those of teamwork and team-based learning in medicine and medical education. They call for research to investigate this, to provide evidence to support group review, and to determine whether specific paper types would benefit most from team review (e.g., particularly complex manuscripts, those receiving widely disparate initial individual reviews). In addition, the authors propose ways in which a team-based approach to peer review could be expanded by journals and institutions. They believe that exploring the use of group peer review potentially could create a new methodology for skill development in research and scholarly writing and could enhance the quality of medical education scholarship.